Association between Alcohol Use and Cardiovascular Self-Care Behaviors among Male Hypertensive Veterans Affairs Outpatients: A Cross-Sectional Study. Issue 1 (January 2015) - Rittmueller, Stacey E.; Frey, Madeleine S.; Williams, Emily C.; Sun, Haili; Bryson, Chris L.; Bradley, Katharine A.
Background: Alcohol use is associated with health behaviors that impact cardiovascular outcomes in patients with hypertension, including avoiding salt, exercising, weight management, and not smoking. This study examined associations between varying levels of alcohol use and self-reported cardiovascular health behaviors among hypertensive Veterans Affairs (VA) outpatients. Methods: Male outpatients with self-reported hypertension from 7 VA sites who returned mailed questionnaires ( N = 11, 927) were divided into 5 levels of alcohol use: nondrinking, low-level use, and mild, moderate, and severe alcohol misuse based on AUDIT-C (Alcohol Use Disorders Identification Test—Consumption) scores (0, 1–3, 4–5, 6–7, and 8–12, respectively). For each category, adjusted logistic regression models estimated the prevalence of patients who self-reported avoiding salt, exercising, controlling weight, or not smoking, and the composite of all four. Results: Increasing level of alcohol use was associated with decreasing prevalence of avoiding salt, controlling weight, not smoking, and the combination of all 4 behaviors ( P values all <.001). A linear trend was not observed for exercise ( P =.83), which was most common among patients with mild alcohol misuse ( P =.01 relative to nondrinking). Conclusions: Alcohol consumption is inversely associated with adherence to cardiovascular self-care behaviors among hypertensive VA outpatients. Clinicians should be especially aware of alcohol use level among hypertensive patients.